Niqāt al-Iltiqā’ bayn Madhhad al-Taḥdīth al-Jadīd wa al-Ittijāh al-Taqlīdī al-Mutaṭawwir al-Judhūr al-Ma’rifīyah li Madhhab al-Jawharīyah al-Islāmīyah wa Intishāruhāfī Indūnīsīyā - Ala, Abdul (Studia Islamika, 2004)
The roots of neos-modernism- a school of thought in Islam that was succesfull in Indonesia in the 1980s-strongly relate to Islamic liberalism. This reality requires us to link recent discussions about liberal Islamic discourse with discussions on neo-modernism.  The issue modernism must be addressed, because it is able to attract the attention of leaders of the Islamic community from various school of thought.DOI: 10.15408/sdi.v11i1.654